Correlation of Microplastic Levels with Erythrocyte Profiles in Wistar Rats Orally Exposed to Polyethylene Microplastics - I Komang Andriana Yastalasmana; Niluh Suwasanti; Yudhiakuari Sincihu; Mulya Dinata; Bernadette Dian Novita Dewi (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Polyethylene microplastics are widely used in single-use products and can enter the body through contaminated food or beverages. After ingestion, these particles may cross the intestinal barrier and reach systemic circulation. Their presence in blood is suspected to induce oxidative stress through increased reactive oxygen species, potentially affecting erythrocyte membrane integrity. Erythrocytes are essential for oxygen transport, and structural damage may reduce their flexibility and lead to morphological abnormalities. This study aimed to evaluate the correlation between microplastic counts in blood and erythrocyte profiles in Wistar rats exposed orally to polyethylene microplastics. A quantitative experimental study with a post-test only control group design was conducted. Male Wistar rats were assigned to one control group and three exposure groups receiving different microplastic doses for four weeks. Microplastics were identified using light microscopy and Fourier Transform Infrared spectroscopy, while erythrocyte profiles were assessed through peripheral blood smears and hematological examination. Microplastics were detected in exposed groups, accompanied by several abnormal erythrocyte forms. However, no significant differences or correlations were observed between microplastic counts and erythrocyte parameters. Oral exposure to polyethylene microplastics did not significantly alter erythrocyte profiles, although potential morphological effects cannot be excluded.